Pengaruh Faktor Fundamental Keuangan dan Makro Ekonomi Terhadap Harga Saham pada Perusahaan Badan Usaha Milik Negara (BUMN) yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2016-2020 - Fabiola Dinda Effendi; Tantina Haryati (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
Stock investment in the capital market promises two forms of profit, capital gains and dividends. In addition to high profits, stock investments also have a high risk of loss because stocks have a nature high return-high risk. One of the risks posed is the ups and downs of stock prices that occur at any time can cause losses such as capital loss. The purpose of this study was to determine the effect of ROE, DER, and exchange rates on stock prices in BUMN listed on the Indonesia Stock Exchange (IDX) for the 2016-2020 period. The sampling technique is a purposive sampling technique. The sample obtained amounted to 13 companies. The results of the analysis using SmartPLS 3.0 shows that ROE has a positive and significant effect, DER has a negative and significant effect, while the exchange rate has no significant effect on stock prices.